Influence of Teacher Training Programs on Quality of Education in South Africa - Ngubane, Thabo (African Journal of Education and Practice, 2024)
Purpose: The aim of the study was to investigate the influence of teacher training programs on quality of education in South Africa. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Enhanced teacher training programs in South Africa significantly improve educational outcomes, particularly in math and science. However, disparities in training quality across regions impact effectiveness. Standardizing high-quality training is crucial for boosting educational standards nationwide. Unique Contribution to Theory, Practice and Policy: Pedagogical content knowledge (PCK), transformative learning theory & social constructivism may be used to anchor future studies on influence of teacher training programs on quality of education in South Africa. Facilitates the development of teaching materials that reflect local realities, which can improve student comprehension and retention. Promotes policies that require teacher training programs to include a significant component of local content, ensuring education is contextually relevant.